2019
DOI: 10.1111/jora.12529
|View full text |Cite
|
Sign up to set email alerts
|

Religious Social Support Protects against Social Risks for Adolescent Substance Use

Abstract: We used a social developmental perspective to identify how prominent social contexts influence substance use during adolescence. Longitudinal data were collected annually from 167 parent-adolescent dyads over four years. We investigated whether parent substance use was related to adolescent substance use directly and indirectly via peer substance use and whether these associations were moderated by religious social support. Structural equation modeling (SEM) analysis indicated significant moderated mediation: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Other longitudinal research has shown that religious social support can moderate adolescent substance use. Specifically, adolescents who believed that their peers used illicit substances refrained from later using these substances themselves, but only if they reported high levels of religious social support (Peviani et al, 2020).…”
Section: Understanding the Link Between Greater Religiousness And Low...mentioning
confidence: 99%
“…Other longitudinal research has shown that religious social support can moderate adolescent substance use. Specifically, adolescents who believed that their peers used illicit substances refrained from later using these substances themselves, but only if they reported high levels of religious social support (Peviani et al, 2020).…”
Section: Understanding the Link Between Greater Religiousness And Low...mentioning
confidence: 99%
“…Researchers have noted, for example, that adolescents are often socialized by members of their religious group to avoid harmful substances (Smith, 2003). Religious beliefs and group membership also provide moral directives (Pearce, Uecker & Denton, 2019; Smith, 2003); promote social bonds, emotional regulation, and delay discounting (Dougherty et al, 2014); furnish positive role models (Pearce, Uecker & Denton, 2019); teach adolescents how to cope with stressful situations (Soenke, Landau & Greenberg, 2013); provide social support (Peviani, Brieant, Holmes, King-Casas, & Kim-Spoon, 2020); and prepare them to process and manage negative emotions (Asma, 2018). Several of these factors, in turn, are associated with a lower risk of substance use problems (Allen & Lo, 2010; Holmes & Kim-Spoon, 2016).…”
Section: Introductionmentioning
confidence: 99%